Changing Trends In Restaurant Business In Goa (International Journal of Food and Nutritional Sciences, 2022)
The Restaurants industry in India has been growing at a rapid rate over the last decade and the growth trend is set to continue. Restaurant have witnessed an era of new trends apart from the usual, fine dining, casual dining, food trucks etc. Restaurants are serving their customer digitally through digital apps or third -party service, this is an easy way to deliver the food on time and provides opportunity to grow in the restaurant industry. The restaurants in Goa in recent years have also been adopting foreign food cuisine since there is a lot of foreign tourists. As the foreign cultures and food has made an impact on Goan cuisine, the people of Goa are curious to try out foreign dishes. Goa offers an array of cuisines to its local, domestic and overseas customers. The present paper provides an overview of the changing trends in restaurant business in Goa, based on data collected from 40 restaurants in Goa. A more detailed study of various apps preferred by restaurants and customers can be undertaken for research.